2002
DOI: 10.1007/s00109-001-0287-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of a functional inducible nitric oxide synthase promoter variant with complications in type 2 diabetes

Abstract: Complications of diabetes have a genetic influence. Since increased inducible nitric oxide synthase (iNOS) gene ( NOS2A) expression can contribute to tissue damage, NOS2A is a worthy candidate for such a role. We therefore tested a 4-bp insertion/deletion (+/-) polymorphism 0.7 kb upstream of NOS2A for association with complications in type 2 diabetes patients, and also performed transient transfection experiments to examine the effect of this variant on promoter activity in kidney cells in culture. We investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…The activation of NOS-2 and the subsequent production of large amounts of free radical gas NO is an important anti-infectious and anti-tumor mechanism of innate immunity. However, overproduction of NO has been implicated in several pathological conditions that include (but are not limited to) the following: 1) tissue injury and various inflammatory disorders (11,12); 2) neuronal disease (13,14); 3) auto-immune diseases (15, 16); 4) cancer or tumor cell proliferation (17, 18); 5) angiogenesis and related pathological changes (19,20); and 6) diabetes mellitus (21,22).…”
Section: Enzymatic Synthesis Of No and Nos-2mentioning
confidence: 99%
“…The activation of NOS-2 and the subsequent production of large amounts of free radical gas NO is an important anti-infectious and anti-tumor mechanism of innate immunity. However, overproduction of NO has been implicated in several pathological conditions that include (but are not limited to) the following: 1) tissue injury and various inflammatory disorders (11,12); 2) neuronal disease (13,14); 3) auto-immune diseases (15, 16); 4) cancer or tumor cell proliferation (17, 18); 5) angiogenesis and related pathological changes (19,20); and 6) diabetes mellitus (21,22).…”
Section: Enzymatic Synthesis Of No and Nos-2mentioning
confidence: 99%
“…is a predominantly transcriptionally regulated gene 21 -24 and promoter variants have been associated with various diseases, including complications in type II diabetes, 25 outcome of hepatitis C virus infection, 26 cerebral malaria 27,28 and dementia. 29 Two independent studies have analysed a pentanucleotide repeat in the promoter region for association with MS. 30,31 Neither study found evidence for an association between the repeat and MS in relatively small cohorts.…”
Section: Nos2amentioning
confidence: 99%
“…Further, these values were significantly higher in patients with complications as compared to patients without complications. Abnormal nitric oxide metabolism is related to advanced diabetic complications in type-2 diabetes mellitus, which may be the consequence of increase in inducible nitric oxide synthase gene expression (22).…”
Section: Discussionmentioning
confidence: 99%